Intrinsic fluorescence in Moringa Oleifera seed extract - Namrah Azmi; Sachin Rathod; Bruno Telli Ceccato; Rasmus Kranold Mikkelsen; Jon Otto Fossum (Talanta Open)
Autofluorescence, an intrinsic property of biological molecules that emit light upon excitation, is gaining significance as a noninvasive technique for studying plant-derived bioactive compounds. This phenomenon enables detection of biomolecules such as chlorophyll, lignin, flavonoids, and alkaloids without requiring external dyes or destructive extraction processes. Intrinsic fluorescence can also aid in detecting and identifying biomolecules that typically require extensive sample preparation (molecule labelling with external fluorophores), eliminating the need for external probes. The present study aims to report the intrinsic autofluorescence in the Moringa Oleifera plant, highlighting its potential to enhance noninvasive bioactive compound identification and quality assessment in plant-based products.